Three-Dimensional Computed Tomography of the Detoured Facial Artery: Variations and Implications for Nasojugal Groove Correction. Issue 6 (June 2021) - Cong, Li-Yao; Kong, Xiang-Xue; Luo, Cheng-En; Luo, Sheng-Kang
Abstract : BACKGROUND: When performing filler injection procedures to the nasojugal groove, there is the risk of iatrogenic damage to the detoured facial artery. OBJECTIVE: To determine the 3-dimensional location of the detoured facial artery. MATERIALS AND METHODS: The branches of the facial arteries from 118 cadaveric hemifaces were scanned using computed tomography and reconstructed using the Mimics software program. RESULTS: Detoured facial arteries were found in 47 of the 118 hemifaces (39.8%). Two main arterial patterns were identified: in Type I (29 of 47 cases), there were both detoured and nasolabial trunks where the facial artery originated, whereas in Type II (18 of 47 cases), there was only a detoured trunk. The detoured trunk originated 32.0 ± 5.3 mm from the midsagittal line, 5.0 ± 2.8 mm from the occlusion plane, and 5.9 ± 3.5 mm below the skin layer; the inflection of the detoured trunk was located 30.0 ± 5.6 mm laterally, 26.2 ± 4.4 mm superiorly, and 5.7 ± 2.6 mm deep. The meeting point with the inferior orbital rim plane was located 17.1 ± 3.4 mm laterally, 43.4 ± 3.1 mm superiorly, and 2.8 ± 1.7 mm deep. CONCLUSION: The 3-dimensional location of the detoured facial artery as reported here will help clinicians to avoid iatrogenic damage when they are performing filler injection procedures.